Surgical management of some congenital anomalies in ruminants - Kamal El-Din Hussein (Eurasian Journal of Veterinary Sciences)
Aim: A survey was undertaken to analyze the congenital anomalies in ruminants recorded at in the veterinary college teaching hospital. Materials and Methods: A total of 58 cases (21 atresia ani, 11 atresia recti, 5 atresia ani et recti, 11 urethral dilatation, 2 contracted tendon, 1 hypospadias, 1 supernumerary limb, 3 dermoid cyst, 1 cyclopia, 2 persistent urachus) of congenital malformations were evaluated. Results: A total of 56 congenital malformation cases were operated. Conclusion: The development of these congenital malformations, their effect on the animal life and the different surgical interventions were discussed.